Implementation and performance in New American Schools : three years into scale-up - Berends, Mark, 1962-; Rand Education (Institute) (Santa Monica, Calif. : RAND, 2001)
Spurred by the piecemeal approach to school reform that had produced little change in the nation's test scores, New American Schools (NAS) launched its efforts for whole-school reform in 1991. As a private nonprofit organization, NAS's mission is to help schools and districts dramatically raise the achievement levels of large numbers of students by using whole-school designs and design team assistance during the implementation process. NAS is currently in the scale-up phase of its effort in which the designs are being widely diffused in partnering jurisdictions across the nation. This book provides an overview of the progress in implementation and performance in a longitudinal sample of schools three years into the scale-up phase. It describes trends in implementation, school performance, and related factors for the sample of NAS schools. Overall, the authors' analyses strongly underscore the importance of both the district environment and design team assistance in implementation. Without leadership, support, and availability of resources at the district level; without clear communication, provision of materials and staff support; and without efforts on the part of design teams to build a consensus of teacher support, implementation is likely to fail or at least lag far behind. Their findings also suggest comprehensive school reforms face many obstacles during implementation, and because of this, whole-school designs face continuing challenges in dramatically raising the achievement of all students.
A Brief History of New American Schools and RAND's Role in Monitoring the Effort -- Analyzing Implementation and Performance in NAS Schools: a Conceptual Framework -- RAND's Sample of New American Schools -- Status of Implementation -- Factors Affecting Implementation -- Performance Trends in NAS Schools -- Qualitative Outcome Indicators -- Conclusions and Policy Implications -- Appendix A: Key Studies in RAND's Evaluation of NAS School Reform -- Appendix B: Description of Additional Implementation Indicators of the Designs, by Jurisdiction and Design Team, 1997 and 1998 -- Appendix C: Models of Performance Expectations, Instructional Strategies, and Professional Development and Implementation Indices -- Appendix D: Description of Standardized Tests Used by Various Jurisdictions -- Appendix E: Graphs for Reading Scores for NAS Schools in Everett, Northshore, and Shoreline Districts in Washington -- Appendix F: RAND Principal and Teacher Questionnaires.
"Prepared for New American Schools."
"This report was written under the aegis of RAND Education"--Page iv.
Includes bibliographical references (pages 245-257).
Print version record.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
Keywords: New American Schools (Organization); New American Schools (Organization); School improvement programs -- United States -- Longitudinal studies; Educational change -- United States -- Longitudinal studies; Enseignement -- Réforme -- États-Unis -- Études longitudinales; EDUCATION -- Administration -- General; Educational change; School improvement programs; United States; Theory & Practice of Education; Education; Social Sciences; Längsschnittuntersuchung; Schulentwicklung; USA; Longitudinal studies